Robotic Technologies for Non-Standard Design and Construction in Architecture - José Pedro Sousa (2017)
In November 2015, the Faculty of Architecture at the University of Porto and the Institute for Systems and Computer Engineering, Technology and Science concluded a 2-year research project on the use of robotic fabrication technologies in architecture and building construction. Funded by the national Foundation of Science and Technology, this was a unique and vibrant experience on a new research field for the two institutions. This paper provides a brief description of the research project and its results.